Digital Technology, Cost Category, and Competitive Advantage in Islamic Bank X - Fatchullah Reza Siswanto; Nazaruddin Malik; Driana Leniwati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study conducted an in-depth analysis of the competitive advantage and costs of implementing digital technology in Islamic bank X. There are differences in the use of digital technology by individual and corporate customers. Individual customers mostly use mobile and Internet banking, whereas corporate customers use a more diverse range of services, such as cash management systems. Qualitative Case study research in Islamic Bank X enables a deeper discussion of cost and competitive advantage, which prior studies have not explored extensively. The informants in this study were key employees and customers who had used digital technology. The results of this study show that three costs arise in the implementation of digital technology: analysis, monitoring, and adjustment costs. The competitive advantage obtained from the implementation of digital technology can be felt by management and customers: data security, operational efficiency, transparency and accountability, product innovation, and customer loyalty. This research contributes to policymaking regarding implementing digital banking technology, which entails cost implications and brings significant advantages for banking sectors.